Environmental Knowledge and Its Impact on Purchase Intention of Eco-Friendly Fashion: A Study among Gen Z and Millennials in Jabodetabek - Syafira, Raissa (Syntax Corporation, 2024)
The fashion industry has now become the second most polluting industry in the world in terms of threatening the environment and resources. This is because the fashion industry creates more harmful gas emissions than the shipping and aviation industries, and disposes of water waste because the manufacturing process requires a lot of clean water. Therefore, it is hoped that the fashion industry will be more concerned about the environment and also the people affected by waste, so that the business processes carried out can contribute to the environment. Some of the serious impacts of environmental damage are global warming, increasing environmental pollution, and decreasing flora and fauna. This research uses a hypothesis testing research design by testing the variables Social Responsibility, Environmental Apparel Knowledge Trust, Attitude and Perceived Consumer Effectiveness on Purchase Intention among sustainable fashion consumers. In this study, to collect data using the method of distributing questionnaires to 191 respondents in Jabodetabek. In this research, validity and reliability testing will be carried out using SPSS 25 and this research will use SEM analysis and the data will be processed using Smart PLS. This research found that there is a positive influence of Social Responsibility and Environmental Apparel Knowledge on Trust, Attitude and Perception. Consumer Effectiveness and there is a positive influence of Trust, Attitude and Perceived Consumer Effectiveness Purchase Intention on sustainable fashion consumers.